Self-Help-Plus: Making a Difference for Vulnerable Women. Issue 5 (September 2020) - Callister, Lynn Clark
Abstract : There are women globally whose life experiences have been different than many of our own: women who have experienced or witnessed horrible traumatic events; women who struggle with overwhelming poverty, lack of inadequate housing and food insecurity; women who live in places where chronic endemic violence and armed conflict exists; women living in places where there are extensive humanitarian needs; and women who are displaced, forgotten and alone. Our global health and nursing expert, Dr. Callister, discusses one of the low-intensity psychological interventions for women in need developed by the World Health Organization.